2021
DOI: 10.1021/acsami.0c20825
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Functionalized Boron Nanoparticles with Reduced Oxide Content by Nonthermal Plasma Processing for Nanoenergetic Applications

Abstract: The development of an in situ nonthermal plasma technology improved the oxidation and energy release of boron nanoparticles. We reduced the native oxide layer on the surface of boron nanoparticles (70 nm) by treatment in a nonthermal hydrogen plasma, followed by the formation of a passivation barrier by argon plasma-enhanced chemical vapor deposition (PECVD) using perfluorodecalin (C 10 F 18 ). Both processes occur near room temperature, thus avoiding aggregation and sintering of the nanoparticles. High-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…Typically, an effective modication strategy is to produce core/shell nano-structural derivatives. 79,84,[133][134][135][136][137][138] The derivatives usually consist of 0D boron nanomaterials as the core and other inorganic nanomaterials as the shell. Walton et al prepared boron core silica shell (B@SiO 2 ) nanoparticles, having spherical, monodisperse and water-dispersible features suitable for the aforementioned biomedical applications.…”
Section: Core/shell Nano-structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, an effective modication strategy is to produce core/shell nano-structural derivatives. 79,84,[133][134][135][136][137][138] The derivatives usually consist of 0D boron nanomaterials as the core and other inorganic nanomaterials as the shell. Walton et al prepared boron core silica shell (B@SiO 2 ) nanoparticles, having spherical, monodisperse and water-dispersible features suitable for the aforementioned biomedical applications.…”
Section: Core/shell Nano-structuresmentioning
confidence: 99%
“…Agarwal et al reported that the native oxide layer (B 2 O 3 ) on the surface of BNPs (70 nm) was reduced through treatments in a nonthermal hydrogen plasma, followed by forming a passivation barrier (C x F y ) by Ar plasma-enhanced chemical vapor deposition using peruorodecalin C 10 F 18 . 135 Both steps occur near RT, which avoids aggregation and sintering of the core-shell surface-functionalized BNPs (Fig. 11b).…”
Section: Core/shell Nano-structuresmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 8 The melting of the oxide shell before the solid core clogs the pores leads to particle agglomeration and acts as a diffusion barrier to the incoming oxidizer, thus delaying the boron (B) oxidation. 1 , 5 Attempts to overcome these limitations include surface functionalization of B by organic compounds, 9 14 reduction of the oxide, followed by surface passivation using nonthermal plasma processing, 15 and coating with metals to form composites and metal borides by ball milling and high-temperature sintering methods. 16 23 Functionalization with organic compounds results in the reduction of the amount of energy released per unit mass due to the presence of less energetic materials on the B surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pickering et al reported the room-temperature synthesis of organo-capped B nanoparticles from liquid B precursors. B particles were coated with metal fluoride and fluorocarbon by a solution-based precipitation method and nonthermal plasma processing, and they show better combustion performance. , For covalent functionalization of B, it has been reported that surface-functionalized B particles with alkyl chains are more stable in air and have better dispersion in nonpolar solvents, but these alkyl-functionalized B particles have not been incorporated in HTPB or other polymer composites. As for B/HTPB composites, modifications on B particles with fluorides and glycidyl azide polymer were shown to tailor the combustion behavior of the B/AP/HTPB propellant, , but the interactions between the B particles and HTPB were not discussed, and the effects on mechanical properties were not investigated.…”
Section: Introductionmentioning
confidence: 99%